Francesco, giullare di Dio = [videorecording (DVD)] : The flowers of St. Francis - Rossellini, Roberto, 1906-1977; Rossellini, Roberto, 1906-1977; Gerardi, Nazario; Pisacane, Severino; Bonaventura, Esposito; Brunette, Peter; Bazin, André, 1918-1958 (Criterion collection, 2005)
"In a series of simple and joyous vignettes, director Roberto Rossellini and co-writer Federico Fellini lovingly convey the universal teachings of The People's Saint: humility, faith, and sacrifice. Gorgeously photographed to evoke the medieval paintings of Saint Francis' time, and cast with monks from the Nocera Inferiore Monastery"--Container.